Factors associated with physical activity time among adolescents in Ho Chi Minh City, Vietnam - Phung, Vinh Quang; Nguyen, Vien Truong; Nguyen, Ngoc-Trinh Thi; Tran, Dang Ngoc; Nguyen, Phong Duy; Tang, Hong Kim (International Journal of Public Health Science (IJPHS), 2025)
Previous studies on factors associated with physical activity among adolescents in Ho Chi Minh City have lacked a specific framework. This study aimed to assess factors associated with moderate and vigorous physical activity time among Ho Chi Minh City’s adolescents. We used the Health Belief Model to develop a more comprehensive survey. This cross sectional study, conducted from January to May 2023, analyzed data from 301 students. Variables were measured using a self-management questionnaire with three sections: socioeconomics, physical activity, and the Health Belief Model. This study found that adolescents spent an average of 54.7 minutes per day engaging in moderate to vigorous physical activity. This duration was independently associated with convenience (Coefficient = 5.49; p = 0.002), self-efficacy (Coefficient = 5.63; p<0.001), having an exercise companion (Coefficient = 16.98; p<0.001), and the perception that more than 60 minutes of daily activity is needed (Coefficient = 16.82; p<0.001). The Health Belief Model has the potential to explain the time spent in moderate to vigorous physical activity among adolescents in Ho Chi Minh City. Self-efficacy, convenience, companionship, and perceptions of appropriate physical activity duration should be considered when developing intervention programs.